Pengaruh Kemampuan Sumber Daya Manusia, Kualitas Sistem Informasi Akuntansi, dan Budaya Organisasi terhadap Kualitas Laporan Keuangan pada Lembaga Perkreditan Desa (LPD) di Kota Denpasar - Pramanaswari, A.A. Sagung Istri; Sari, Desak Made Mya Yudia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of human resource capabilities, the quality of accounting information systems, and organizational culture on the quality of financial statements in LPD in Denpasar City. The population in this study is all employees at LPD in Denpasar City which totals 557 people. The sample in this study is the accounting section which totals 34 people. The data analysis technique used in this study is multiple linear regression analysis technique. Based on the results of the hypothetical test using the partial t-test, it was concluded that the ability of human resources had a negative effect on the quality of financial statements at the Village Credit Institution (LPD) in Denpasar City. The quality of accounting information systems has a negative effect on the quality of financial reports at Village Credit Institutions (LPD) in Denpasar City. Organizational culture has a positive effect on the quality of financial reports at Village Credit Institutions (LPD) in Denpasar City.